Evaluation of Biomass Yield and Nutritional Composition of Soybean (Glycine max (L.) Merrill) Varieties Grown in Lowland Areas of Eastern Amhara, Ethiopia - Asres, Abito; Tiruneh, Solomon (Department of Agronomy and Horticulture, IPB University, 2025)
This study was conducted to identify the best performing soybean varieties for biomass yield, chemical composition, haulm and seed yield, and other agronomic characteristics under rain-fed conditions in the lowland areas of Eastern Amhara, Ethiopia. The experiment took place at three locations: Jari, Chefa, and Sirinka. A randomized complete block design with three replications was employed. Twelve released soybean varieties “Afgat”, “Belesa-95”, “Boshe”, “Cheri”, “Dhidhessa”, “Gishama”, “Gizo”, “Korme”, “Pawe-03”, “Katta”, “Wegayen”, and “Wollo” served as treatments. Seeds were sown with a spacing of 40 cm between rows and 10 cm between plants. Each plot measured 3.2 m × 4 m, with 0.5 m and 1 m separating plots and blocks, respectively. Combined analyses across Jari and Sirinka indicated that the varieties “Afgat”, “Gishama”, “Gizo”, “Pawe-03”, “Wegayen”, and “Wollo” produced higher dry matter yields than others. “Gishama”, “Gizo”, “Pawe-03”, and “Wegayen” also had superior haulm yields. For seed yield, “Pawe-03”, “Gizo”, “Afgat”, “Gishama”, “Wollo”, and “Wegayen” outperformed the other varieties. Notably, the “Wollo” variety exhibited the highest protein content at both Jari and Sirinka. Based on these results, “Afgat”, “Pawe-03”, and “Wollo” are recommended for cultivation in the Jari, Chefa, and Sirinka zones. These varieties demonstrate strong potential for delivering high dry matter, haulm, and seed yields, as well as providing a valuable protein supplement for ruminants. Further research is recommended to investigate their optimal application in livestock feeding systems.